1982
DOI: 10.1037/0735-7028.13.5.639
|View full text |Cite
|
Sign up to set email alerts
|

Postdivorce family therapy: Suggestions for professionals.

Abstract: The literature describing the stress experienced by family members in the postdivorce transition is reviewed. Suggestions are made for postdivorce family therapy oriented toward helping both ex-spouses continue meaningful involvement with their children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Once again, a number of approaches are possible, including the addition of the noncustodial mother into family therapy with the stepmother family and separate work with the child and noncustodial mother. Moreland, Schwebel, Fine, and Vess (1982) advocate "postdivorce family therapy" that attempts to increase ex-spouse cooperation in child-rearing activities and to improve the quality of parent-child communication. The authors caution that such an approach is not indicated when both spouses are not able or do not desire to cooperate or when one of the parents has severe psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Once again, a number of approaches are possible, including the addition of the noncustodial mother into family therapy with the stepmother family and separate work with the child and noncustodial mother. Moreland, Schwebel, Fine, and Vess (1982) advocate "postdivorce family therapy" that attempts to increase ex-spouse cooperation in child-rearing activities and to improve the quality of parent-child communication. The authors caution that such an approach is not indicated when both spouses are not able or do not desire to cooperate or when one of the parents has severe psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not gather data directly related to the effects of parental differences, but previous research (Hetherington et al, 1976) suggests that those parents who cope more effectively with the stresses of divorce have healthier relationships with their children. In an earlier article, the present authors (Moreland, Schwebel, Fine, & Vess, 1982) discussed several individual differences among parents that affect the course of the adjustment to divorce.…”
Section: Discussionmentioning
confidence: 99%
“…Divorcing couples seeking simply to settle matters and to have little to do with each other in the future are well served by divorce mediation. However, those who will continue to interact, because of their children, for example, may decide that it is important to put aside or learn to deal with some differences so that they can establish an effective, but much more limited relationship (Moreland, Schwebel, Fine, & Vess, 1982). In such circumstances, PMI is appropriate because it addresses issues that might otherwise defeat their efforts to establish a circumscribed relationship.…”
Section: The Psychological/mediation Intervention Modelmentioning
confidence: 99%